A Thermochemical Heat Storage System for Households Combined Investigations of Thermal Transfers Coupled to Chemical Reactions - Fopah Lele, Armand; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The book offers a comprehensive report on the design and optimization of a thermochemical heat storage system for use in buildings. It combines theoretical and experimental work, with a special emphasis on model-based methods. It describes the numerical modeling of the heat exchanger, which allows recovery of about two thirds of the waste heat from both solar and thermal energy. The book also provides readers with a snapshot of current research on thermochemical storage systems, and an in-depth review of the most important concepts and methods in thermal management modeling. It represents a valuable resource for students, engineers and researchers interested in thermal energy storage processes, as well as for those dealing with modeling and 3D simulations in the field of energy and process engineering.
General Introduction -- State-Of-Art of Thermochemical Heat Storage Systems -- Thermal Management Modelling in Thermo-Chemical Heat Storage Systems -- Characterization of Thermal Transfers and Chemical Kinetics -- Performance Analysis of the Thermochemical Heat Storage System -- Conclusion & Guidelines.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Energy storage; Environmental engineering; Biotechnology; Bioremediation; Chemistry, Technical; Engineering Thermodynamics, Heat and Mass Transfer; Mechanical and Thermal Energy Storage; Environmental Engineering/Biotechnology.; Industrial Chemistry